Dos aproximaciones a la noción de infinito en Levinas. - MEDINA, JORGE (Anuario Filosófico, 2023)
In this paper I will try to demonstrate how two fundamental notions in Levinas' ethics, the of idea God and responsibility, can be understood respectively as actual and potential infinity, according to the classic distinction suggested by Aristotle. In addition, I will show that both infinities can exist (something that classical metaphysics did not admit) as long as they are comprehended from an ethics of alterity.